Detection of antimitochondrial antibody by dot-immunobinding assay in patients with primary biliary cirrhosis who tested negative by immunofluorescent staining - KITAMI, Noriyuki; SAKAKIBARA, Yuji; ISHII, Hideo; USUI, Koh (Kanzo, 1989)
Detection of antimitochondrial antibody (AMA) is useful for diagnosis of primary biliary cirrhosis (PBC). Although immunofluorescent techniques are widely used for the detection of AMA, their sensitivity and specificity are not sufficient. We developed a dot-immunobinding assay for AMA using aspirating microplate. This assay method is as sensitive and specific as the immunoblot method. Using this dot-immunobinding method, we observed six patients who tested negetive results for AMA by immunofluorescent staining. The sera of all patients tested positive by the dot-immunobinding assay with varied titer. The clinical course could be followed in three cases and positive results for AMA continued during observation, even though immunofluorescent results became negative. These results suggest that the dot-immunobinding assay is a sensitive and specific technique detecting AMA in PBC.